How genealogy reveals the changing relationship between people and their use of recreational public space - Mdzeke, Nandipha (My University, 2011)
The public space is and has been an integral part of communities for centuries. It serves as a convenient setting for a broad variety of leisure and recreational activities, as well as enhancing the image and perceived value of a community. Recreational public spaces provide a location for people to meet, relax, and exchange ideas. They can serve the needs and interests of all kinds of people, young and old irrespective of their cultural backgrounds. This report seeks to trace the genealogy of people and their use of recreational public space. Thus it uncovers the history of how space is perceived, interpreted and understood by people who live in Yeoville. It focuses on the understanding of space as an agglomeration of people, objects and events.The report also seeks to conceptualize people’s perception on the use of recreational public space and explore the changing relationship between people and their use of space in Yeoville. Through the process of perception we create a sense of place, i.e. a relationship within a specific context. If a place is memorable, it is because it carries perceptual attributes such as clarity, differentiation, uniqueness, structure and form. Planning practice seems to overlook the importance of incorporating genealogy into planning for diversified cultural communities. The use of narratives or storytelling can have a great significance for planners when planning for these communities. Identifying the core components of a Good City Form and the production of space, the paper goes on to connect these elements based Lynch’s theory of ‘Good City Form’ which was propounded in 1981 and also Lebfebvre’s theory on ‘The Production of Space’ (1991), translated from La production de l’espace(1974). Lynch’s Good City Form (1981) form the theoretical base for this report as his five performance dimensions are used to measure whether Yeoville does meet the criteria.
Keywords: Public spaces; multiculturalism